2021
DOI: 10.37213/cjal.2021.31183
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Input-based and Output-based Tasks on L2 Vocabulary Learning

Abstract: This paper reports on a quasi-experimental study that explored the differential effects of input- and output-based tasks on L2 vocabulary learning. The study adopted a pretest- posttest within-participants design, with sixty Vietnamese EFL university students. Participants in the experimental group completed four input and four output tasks in an online learning environment. The target items (ten single words and ten compounds) were counterbalanced across the tasks. The study measured vocabulary gains at four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…To date, a range of topics related to vocabulary in ELT in Vietnam have been investigated, among which vocabulary knowledge of Vietnamese EFL learners has attracted considerable attention (Dang, 2020;Tran, 2013;. In addition, vocabulary learning has been investigated in relation to extensive reading , audiovisual input (D. C. Nguyen & Boers, 2019), input-based and output-based tasks (Duong et al, 2021a(Duong et al, , 2021b, computer-assisted language learning (Bui et al, 2019), and explicit instruction (D. T. Le et al, 2017). These studies, while still limited in quantity, have revealed intriguing findings that have significant implications for ELT stakeholders in Vietnam.…”
Section: )mentioning
confidence: 99%
See 3 more Smart Citations
“…To date, a range of topics related to vocabulary in ELT in Vietnam have been investigated, among which vocabulary knowledge of Vietnamese EFL learners has attracted considerable attention (Dang, 2020;Tran, 2013;. In addition, vocabulary learning has been investigated in relation to extensive reading , audiovisual input (D. C. Nguyen & Boers, 2019), input-based and output-based tasks (Duong et al, 2021a(Duong et al, , 2021b, computer-assisted language learning (Bui et al, 2019), and explicit instruction (D. T. Le et al, 2017). These studies, while still limited in quantity, have revealed intriguing findings that have significant implications for ELT stakeholders in Vietnam.…”
Section: )mentioning
confidence: 99%
“…To date, such studies have focused on the effects of different types of input D. C. Nguyen & Boers, 2019), focused tasks (Duong et al 2021a(Duong et al , 2021b, computer-assisted language learning (Bui et al, 2019), and explicit instruction (D. T. Le et al, 2017) on Vietnamese EFL learners' vocabulary acquisition.…”
Section: Research Into Vietnamese Efl Learners' Vocabulary Acquisitionmentioning
confidence: 99%
See 2 more Smart Citations